Finding Gideon - Dickey, Eric Jerome (New York, New York : Dutton, 2017)
"A professional job turns personal for jet-setting contract killer Gideon in this sexy, thrilling page-turner by New York Timesbestselling author Eric Jerome Dickey. As a hit man from the time he was very young, money, women, and danger have always ruled Gideon's life; but for the first time, the job is taking its toll. Neither Gideon nor the city of Buenos Aires has recovered from the mayhem caused during Gideon's last job. But before the dust has settled and the bodies have been buried, Gideon calls in backup--including the lovely Hawks, with whom Gideon has heated memories--to launch his biggest act of revenge yet. one he believes will destroy his adversary, Midnight, once and for all. Yet Midnight and his second-in-command, the beautiful and ruthless Senorita Raven, are launching their own revenge, assembling a team of mercenaries the likes of which the world has never seen"--
Kirkus Reviews
Booklist
Library Journal Prepub Alert
Keywords: African American men -- Fiction; Assassins -- Fiction; Suspense fiction